Polyinfection secondary to exogenous lipoid pneumonia caused by aspiration of paraffin oil: a Case Report - Yan, Xiaoru; Chen, Xun; Zhu, Yanan; Chen, Shu; Meng, Xiangrui; Li, Jie; Tang, Yufeng; Zhang, Wei; Yi, Liang; Fu, Yan (Frontiers in Medicine, 2025)
BackgroundExogenous lipoid pneumonia is a rare condition caused by the aspiration of lipid-containing substances. Its diagnosis can be challenging due to non-specific respiratory symptoms and imaging findings. Complications, such as secondary infections, may exacerbate the clinical course, particularly in immunocompromised or elderly patients. No cases of ELP complicated by concurrent viral (SARS-CoV-2), bacterial, and fungal infections have been reported in recent literature.Case PresentationWe present the case of a 90-year-old female who developed ELP following the use of oral paraffin oil for ileus management. Initial symptoms included fever, cough, and respiratory distress, with rapidly worsening dyspnea. A chest CT revealed fat-density consolidations. Lipid droplets and lipid-laden macrophages were found in the bronchoalveolar lavage fluid. Her condition was further complicated by polymicrobial infections, including SARS-CoV-2, Mycobacterium abscessus, Klebsiella pneumoniae, and Candida albicans. A comprehensive treatment approach combining antibiotics, antifungals, antivirals, and corticosteroids resulted in significant clinical and radiological improvement over 1 week.ConclusionThis case underscores the importance of early recognition of ELP, particularly in high-risk populations, and highlights the need for a multidisciplinary approach to manage secondary infections. Systemic corticosteroids and tailored antimicrobial therapy proved effective in this critically ill patient.